2014
DOI: 10.1177/1420326x14525061
|View full text |Cite
|
Sign up to set email alerts
|

The application of analytic hierarchy process in daylighting performance assessment

Abstract: Daylighting is beneficial to humans and the environment. Various indicators have been proposed to evaluate its attributes. Studies on the weighting factors of these attributes are, however, sparse. This paper aims to develop a new daylighting performance assessment method by collecting the perceived importance of the attributes from occupants using the analytic hierarchy process (AHP) based on two equally important criteria -visual comfort and electric lighting energy saving potential. The study has two parts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Applied pairwise comparisons between visual comfort criteria in matrix B were also specified by conducting a literature study. The results presented by previous studies showed that the amount of daylight (H (ill.500) in this study) is more important than glare (H (DGI.22) in this study) to a small degree (Chung & Ng, 2016), while it is slightly more important than uniformity (U in this study) (Chung & Ng, 2016). The CR calculated for matrix B was approximately 0.1, which means that applied pairwise comparisons between visual comfort criteria were consistent.…”
Section: Post-processing Phasesupporting
confidence: 77%
“…Applied pairwise comparisons between visual comfort criteria in matrix B were also specified by conducting a literature study. The results presented by previous studies showed that the amount of daylight (H (ill.500) in this study) is more important than glare (H (DGI.22) in this study) to a small degree (Chung & Ng, 2016), while it is slightly more important than uniformity (U in this study) (Chung & Ng, 2016). The CR calculated for matrix B was approximately 0.1, which means that applied pairwise comparisons between visual comfort criteria were consistent.…”
Section: Post-processing Phasesupporting
confidence: 77%
“…Certainly the use of AHP in the selection of interior lighting systems is not a novel issue [16]- [18]. However, the relevance of this study relies in the combination of economic criteria (such as life-cycle cost) and energy saving along with luminaires characteristics (such as lifespan and color rendering) and other lighting parameters previously simulated (e. g. illuminance, power consumption, uniformity, glare, and energy efficiency).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix C shows the pairwise comparisons performed among the visual comfort criteria. According to Chung and Ng [39], H illu > 500 is to a small degree more important than H DGI>22 . The weight of the criteria was calculated following the three above-mentioned steps.…”
Section: First Scenariomentioning
confidence: 99%